116 Subclinical myocardial inflammation in asymptomatic men living with HIV (MLWH): H-art to heart sub-study. (17th July 2020) - Manmathan, Gavin; Ngwu, Nnenna; Johnson, James; Little, Callum; Kotecha, Tushar; Hemat, Nargis; Chacko, Liza; Adam, Sana; Kinloch, Sabine; Barber, Tristan; Burns, Fiona; Fontanna, Marianna; et al.
Abstract : Introduction: Human immunodeficiency virus (HIV)/ acquired immune deficiency syndrome (AIDS) was traditionally associated with severe heart failure, pulmonary hypertension and myocarditis but this is rarely seen following the advent of antiretroviral therapy (ART). Previous studies in asymptomatic people living with HIV (PLWH) have revealed a high burden of cardiovascular disease (CVD), and subclinical myocardial inflammation as detected by cardiac magnetic resonance imaging (CMR). The H-ART to Heart study was designed to assess the prevalence of CVD in PLWH. In this sub-study, we aim to assess bio-markers, structural and functional cardiac changes associated with HIV using CMR. Methods: In this cross-sectional study, we recruited asymptomatic Caucasian men who have sex with men (MSM) diagnosed with HIV > 10yrs ago, aged 35-55 years, with undetectable viral loads on ART. They were compared to HIV-negative age and ethnicity MSM matched controls. Those with Q-Risk3 CVD risk factors (hypertension, hyperlipidaemia, diabetes, smoking, inflammatory arthritis, depression, severe mental illness) or hepatitis co-infection were excluded. Assessments included blood pressure (BP); bloods for inflammation; transthoracic echocardiography for all participants and stress perfusion CMR with multiparametric mapping for PLWH. We compared CMR results with a previously selected control group of healthy volunteers with no cardiovascular risk factors. Results: 45 participants were recruited (26 MLWH; 19 HIV- MSM), mean results for MLWH were as follows: duration of HIV 17.8±6.4yrs, duration on ART 10.7±5.2yrs, nadir CD4 count 318±145 cells/μL, current CD4 count 610±150 cells/μL and current viral load <40 copies/mL . There were no significant differences in baseline data (Table 1 ). Although not significant, detectable inflammatory markers were more prevalent and median levels higher in MLWH. Echocardiogram parameters were similar between groups. Of those who had a Left Ventricular Ejection Fraction (LVEF) <55% (Simpson's Biplane) all 3 (15%) were MLWH (range 47.5-53.1%). CMR data for LVEF was comparable to that reported by echocardiography, most parameters were similar between the groups aside from statistically significant higher T2 (46.2±1.6 v 44.4±2.5ms; P<0.05) and LGE (76.5 v 14.3%; P<0.001) in MLWH (Table 2 ). There was no evidence of ischaemia or myocarditis in either group. Conclusion: From our small study of well treated asymptomatic MLWH with low CVD risk profiles, we were able to detect subtle differences in inflammatory biomarkers compared to controls, However this did not translate to evidence of detectable myocardial pathology classically associated with HIV (cardiomyopathy, myocarditis). There was no difference in LVEF%, LV Mass-I or native T1, a marker of diffuse fibrosis, which is different to previous published data, perhaps due to our strict inclusion criteria. However T2, a more specific marker of myocardial oedema, and more non-specific LGE were detected in MLWH. This may indicate an early signal of myocardial inflammation in well treated MLWH. Conflict of Interest: None